2012
DOI: 10.1002/rra.2617
|View full text |Cite
|
Sign up to set email alerts
|

The Significance of Perceptions and Feedbacks for Effectively Managing Wood in Rivers

Abstract: This article reports a survey of 196 river managers in seven states across the USA assessing their perceptions of in-stream wood. This survey followed corresponding questionnaires given to undergraduate students representing non-expert views in the same states and in 10 countries around the world. Whereas most students registered predominantly negative views of in-stream wood (i.e. not aesthetically pleasing, dangerous and needing improvement), American managers perceive rivers with wood as significantly more … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
33
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(35 citation statements)
references
References 60 publications
2
33
0
Order By: Relevance
“…The use of habitat patches indicated that reconstructed habitats may be used by multiple native species, hence maximising environmental benefits. This can be used to increase the positive perceptions by both the public and managers of the beneficial outcomes from woody-habitat reconstruction as a rehabilitation action (Chin et al 2012). The differences in habitat use shown can be used to design habitats that are more suited to the native species (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…The use of habitat patches indicated that reconstructed habitats may be used by multiple native species, hence maximising environmental benefits. This can be used to increase the positive perceptions by both the public and managers of the beneficial outcomes from woody-habitat reconstruction as a rehabilitation action (Chin et al 2012). The differences in habitat use shown can be used to design habitats that are more suited to the native species (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Wood, both living and dead, is a naturally occurring feature of rivers where it acts as an ecosystem engineer, creating and sustaining habitats that are physically and ecologically diverse (Gurnell et al, ; this volume; Pilotto et al, ) and increasing the availability and diversity of food resources for stream consumers (Cashman et al, ). A growing body of scientific evidence on the multiple co‐benefits of wood in rivers is gradually changing the negative perception that rivers with wood are less attractive (untidy) and more hazardous (Piégay et al, ; Chin et al, ; Wohl, ). As a result, the long‐held practice of removing wood from rivers (Wohl, ), such as to facilitate navigation and increase conveyance of flows and sediments, is now being challenged and there is increasing emphasis on promoting the (re)introduction of instream wood features as part of restoration schemes to assist habitat recovery.…”
Section: Introductionmentioning
confidence: 99%
“…This is a response to the common belief that instream wood is dangerous for both boating and floods (Chin e t al. , ). This perception represents a key threat to the success of resnagging projects (MDBA, ).…”
Section: Introductionmentioning
confidence: 99%